2021
DOI: 10.1042/bsr20211769
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal transaminase and lipid profiles in coexisting diseases in patients with fatty liver: a population study in Sichuan

Abstract: Among chronic liver diseases, fatty liver has the highest incidence worldwide. Coexistence of fatty liver and other chronic diseases, such as diabetes, hepatitis B virus (HBV) and Helicobacter pylori (Hp) infection, is common in clinical practice. The present study was conducted to analyze the prevalence and association of coexisting diseases in patients with fatty liver and to investigate how coexisting diseases contribute to abnormal transaminase and lipid profiles. We enrolled participants who were diagnose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…Therefore, it is challenging to determine patients with a high risk of progression. Recent guidelines suggested a screening system for NAFLD including the use of liver function biomarkers, and variable indices (Giri et al 2022 ; Jiang et al 2021 ; Tokushige et al 2021 ; Kang et al 2021 ). AST/ ALT ratio, TyG index, FLI, and HIS reflected NAFLD in our groups with variable percentages (AST/ALT: 64 versus 56%; TyG index: 92 versus 76%; FLI: 84 versus 64%; HSI: 88 versus 64% in fatty and non-fatty liver groups; respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is challenging to determine patients with a high risk of progression. Recent guidelines suggested a screening system for NAFLD including the use of liver function biomarkers, and variable indices (Giri et al 2022 ; Jiang et al 2021 ; Tokushige et al 2021 ; Kang et al 2021 ). AST/ ALT ratio, TyG index, FLI, and HIS reflected NAFLD in our groups with variable percentages (AST/ALT: 64 versus 56%; TyG index: 92 versus 76%; FLI: 84 versus 64%; HSI: 88 versus 64% in fatty and non-fatty liver groups; respectively).…”
Section: Discussionmentioning
confidence: 99%
“…The above studies all suggest that the prevalence of NAFLD in HBsAg-positive population is lower, which may be related to the involvement of HBV in lipid metabolism in the liver. It was found that HS was positively correlated with the level of triglyceride and low-density lipoprotein cholesterol (LDL-C) and negatively correlated with HBV infection, suggesting that HBV may have the effect of neutralizing lipid metabolism [ 19 ]. Results of a Korean cohort study of non-cirrhotic and non-diabetic adults (n = 62,287) with a 4.46-year follow-up showed that serum HBsAg positivity was negatively correlated with development of hypercholesterolemia, high LDL-C triglyceride, and high non-high-density lipoprotein-cholesterol (non-HDL-C) (aHR = 0.71, 95%CI 0.64–0.79; 0.83 [0.78–0.89]; 0.61 [0.54–0.70]; 0.69 [0.63–0.75]; respectively) [ 20 ].…”
Section: Interaction Between Hbv Infection and Nafldmentioning
confidence: 99%